Rumour Response Strategy And Behavioural Intention: The Mediating Roles Of Anxiety And Government Reputation During Covid-19 “Infodemic” In China - Chen, Guangyu (2023)
The rising popularity of social media has inevitably led to the dissemination of both factual and truthful information as well as rumours. Specifically, numerous health rumours have circulated on digital platforms following the global COVID-19 pandemic. Relevant government bodies must proactively convey public information to influence individuals’ behaviour and subsequent involvement in emergency decision-making during a major health crisis. As such, the right rumour response strategy must be used by the government to avoid negative reaction from the public amidst a major health crisis. This study was based on three key objectives: (i) to identify the most effective government rumour response strategies to address rumours during a health crisis; (ii) to examine the role of anxiety in this process; (iii) to examine the role of government reputation in the process. The Situational Crisis Communication Theory (SCCT) served as the theoretical foundation of the study. Online survey experimental data were collected from 245 Chinese participants, who were exposed to a false social media rumour stimulus that potato chips could spread Covid-19. Notably, the participants were subjected to one of the three following rumour response strategy: denial, refute, and attack. The one-way ANOVA results revealed that the impact of the refutation response led to the lowest rumour dissemination intention. The refutation response also led to the lowest behavioural intention to consume rumour-related products.